Hubungan Sosialisasi Program Jaminan Kesehatan Nasional Terhadap Pengetahuan Hak Peserta BPJS Kesehatan di Puskesmas Kota Padang - Dimas Gusrizal; Febrian Febrian; Aria Fransiska (Faculty of Dentistry Universitas Andalas, 2020)
The socialization about the right of participation has been carried out by BPJS Health to the community at the puskesmas. There are 4 stages in socialization, namely the stages of sensitization, publicity, education, and motivation. The government has determined that all Indonesian citizens must become BPJS Health participants, but socialization to the community is still not optimal, causing many BPJS participants who do not know about their membership rights. The purpose of this study was to find out how the socialization process of the JKN program relates to the knowledge of the rights of BPJS Health participants. The Method of the research is an observational analytic study with a cross-sectional approach. The number of samples is 106 respondents with consecutive sampling techniques. Data were analyzed by Chi-Square test with a p-value <0.05. The results of this study indicate that each stage of socialization is not optimal and results in low knowledge of BPJS Kesehatan participants. The Conclusion is a relationship between the socialization of the National Health Insurance program on the knowledge of the rights of BPJS Health participants at the Padang City Health Center.